A Critical Analysis of Superstitious Business Practices in Strategic Management - Woo, Catherine (2009)
Superstition has a very long history in influencing human behaviours, which implies supernatural beliefs play an significant role in influencing the human decision making process, which affects the way business decisions are made and the formation of strategies in a business context. This influence should not be underestimated, yet this promising area has been ignored by many researchers in the past, so this study investigates the role of superstition in a resource-based approach to business strategy and decision making.